The Relation Between Social Determinant of Health with Access to Health Services in Gonbad kavoos - Masoome Gholami; Amir Ashkan Nasiripoor; Mohammad Reza Maleki (Shahid Beheshti University of Medical Sciences, 2016)
Background and Objective: Today health perpectives has been changing widly. Now social determinants of health are more influence in disease rather than biological causes. If these determinants being ignored, achievement to health Golas would be impossible. This study was conducted to determine the relationship between Social determinants of health and access to health care in GonbadKavoos. Materials and Methods: This study was a correlation and cross-sectional. The populations were urban residents of GonbadKavoos, and the sample size was four hundred households, and the data collection tool was a questionnaire. For statistical analyze between variables these tests were used: independent sample test, Pearson correlation and ANOVA. Results: Among determinants of health, the variables like: socio-economic status of household (P<0.0001), educational level of household breadwinner (P<0.0001), family dimension (P<0.018), employment (P<0.003), residential area (P<0.001), access to internet (P<0.0001), doing exercise (P<0.0001), and having insurance (P<0.0001), had significant relationship with access to health care, spatially dental services and periodical checkup. Conclusion: Social determinants of health have very important relationship with access to health care. Then to decline these inequities in access to health care, development of social and economic equality for all people is so crucial.